Keterwakilan Perempuan dalam Ranah Politik & Urgensi Keterwakilannya: Tinjauan Pengambilan Keputusanya Prespektif Bimbingan Konseling (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
Becoming woman representatives either in politics or other organizations requires good will, self- support, and morality. If necessary, it requires supernatural and spiritual strength. The biggest challenge of woman representatives is how they can maintain their familyâs harmony and unity. This must always be the main target of success of any woman representatives.